2014
DOI: 10.1016/j.msea.2014.04.094
|View full text |Cite
|
Sign up to set email alerts
|

The effects of quench rate and pre-deformation on precipitation hardening in Al–Mg–Si alloys with different Cu amounts

Abstract: The effects of quench rate after solution heat treatment in combination with 1% pre-deformation on precipitation hardening in three Al-Mg-Si alloys have been investigated by transmission electron microscopy and hardness measurements during an isothermal heat treatment. The alloys contain different Cu amounts (up to 0.1 wt%) and the same amounts of other solute elements. While a Cu amount below 0.01wt% does not affect precipitation hardening, an addition of 0.1wt% Cu increases hardness due to formation of a fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…Two different solution-annealing soaking durations of 1 and 20 min were also examined. Since the slower CALVET-type DSC required at least 5 min to achieve thermal equilibration [13], a soaking duration of 1 min is only investigated in the faster DSCs (0.3-5 K/s). Therefore, a systematic investigation of the quench sensitivity or quench-induced precipitation behavior after different solution-annealing conditions was conducted, and the DSC experiments were performed with three significant parameters varied, as follows: Figure 3 highlights one parameter set of the cooling experiments, plotted according to the 540, 550, and 560 • C solution-annealing temperatures.…”
Section: Continuous Heating Of the T651 Initial Conditionmentioning
confidence: 99%
“…Two different solution-annealing soaking durations of 1 and 20 min were also examined. Since the slower CALVET-type DSC required at least 5 min to achieve thermal equilibration [13], a soaking duration of 1 min is only investigated in the faster DSCs (0.3-5 K/s). Therefore, a systematic investigation of the quench sensitivity or quench-induced precipitation behavior after different solution-annealing conditions was conducted, and the DSC experiments were performed with three significant parameters varied, as follows: Figure 3 highlights one parameter set of the cooling experiments, plotted according to the 540, 550, and 560 • C solution-annealing temperatures.…”
Section: Continuous Heating Of the T651 Initial Conditionmentioning
confidence: 99%
“…This is a very complex process, and everything that occurs after extrusion or after the SHT influences the numbers, size distribution and types of metastable precipitates. [5][6][7][8][9] Therefore, parameters such as cooling rate from extrusion or SHT, room temperature (RT) storage time and pre-deformation before AA, as well as AA temperature and time are crucial for the material properties. To be able to optimize properties and design new alloys, the processes happening at the micro-and nanoscale must be studied and understood.…”
Section: Al-mg-si(-cu) (6xxx) Alloys Are Widely Used Inmentioning
confidence: 99%
“…This work focuses on the influence of low amounts of Cu (0.01 at.%/0.03 wt.%) because of a reported considerable effect on precipitation when present in higher concentrations ( 0.4 wt.%) [23,[27][28][29]. Previous studies evaluating the effect of low Cu additions looked at lean extruded alloys ( 0.1 wt.%) [26,30,31]. High-resolution transmission electron microscopy (TEM) studies found that 0.1 wt.% Cu had limited effect on the Al-Mg-Si system precipitation, merely affecting the precipitation kinetics and number densities.…”
Section: Introductionmentioning
confidence: 99%